Optimizing diagnosis of obstructive coronary artery disease by CT angiography: RCT's final results and 12-months follow-up. (25th November 2020) - Dias Ferreira Reis, J.P; Ramos, R; Modas Daniel, P; Aguiar Rosa, S; Almeida Morais, L; Cruz, M; Moreira, R; Mendonca, T; Monteiro, A; Leal, C; Marques, H; Figueiredo, L; et al.
Abstract: Aim: In patients (pts) with suspected coronary artery disease (CAD), computed tomographic angiography (CTA) may improve pt selection for invasive coronary angiography (ICA) as alternative to functional testing. However. the role of CTA in symptomatic pts after abnormal functional test (FT) is incompletely defined. Methods and results: This randomized clinical trial conducted in single academic tertiary center selected 218 symptomatic pts with mild to moderately abnormal FT referred to ICA to receive either the originally intended ICA (n=103) or CTA (n=115). CTA interpretation and subsequent care decisions were made by the clinical team. Pts with high risk features on FT, previous acute coronary syndrome, previously documented CAD, chronic kidney disease (GFR<60ml/min/1.73m 2 ) or persistent atrial fibrillation were excluded. The primary endpoint was the percentage of ICA with no significant obstructive CAD (no stenosis ≥50%) in each group. Diagnostic (DY) and revascularization (RY) yields of ICA in either group were also assessed. Pts were followed up for at least 1 year for the primary safety endpoint of all cause death/ nonfatal myocardial infarction/ stroke. Unplanned revascularization (UP) and symptomatic status (SS) were also evaluated. Pts averaged 68±9 years of age, 60% were male, 29% were diabetic. Nuclear perfusion stress test was used in 33.9% in CTA group and 31.1% in control group (p=0.655). Mean post (functional) test probability of obstructive CAD was 34%. Overall prevalence of obstructive CAD was 32.1%. In the CTA group, ICA was cancelled by referring physicians in 83 of the pts (72.2%) after receiving CTA results. For those undergoing ICA, non-obstructive CAD was found in 5 pts (15.6%) in the CTA-guided arm and 60 (58.3%) in the usual care arm (p<0.001 Mean cumulative radiation exposure related to diagnostic work up was similar in both groups (6±14 vs 5±14mSv, p=0.152). Both DY (84.4% vs 41.7, p<0.001) and RY (71.9% vs 38.8%, p=0.001) yields were significantly higher for CTA-guided ICA as compared to standard FT-guided ICA. The rate of the primary safety endpoint was similar between both groups (1.9% vs 0%, p=0.244), as well as the rates of UP (0.9% vs 0.9%, p=1.000) and SS (persistent angina: 29.6% vs 24.8%, p=0.425). Conclusions: In pts with suspected CAD and mild to moderately abnormal ischemia test, a diagnostic strategy including CTA as gatekeeper is safe, effective and significantly improves diagnostic and revascularization yields of ICA. Funding Acknowledgement: Type of funding source: None